2021
DOI: 10.1016/j.jcv.2021.104984
|View full text |Cite
|
Sign up to set email alerts
|

A combined strategy to detect plasma samples reliably with high anti-SARS-CoV-2 neutralizing antibody titers in routine laboratories

Abstract: The determination of anti-SARS-CoV-2 neutralizing antibodies (NAbs) is of interest in many respects. High NAb titers, for example, are the most important criterion regarding the effectiveness of convalescent plasma therapy. However, common cell culture-based NAb assays are time-consuming and feasible only in special laboratories. Our data reveal the suitability of a novel ELISA-based surrogate virus neutralization test (sVNT) to easily measure the inhibition-capability of NAbs in the plasma of COVID-19 convale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…It can be postulated that part of the antibodies detected by these ELISA are able to interfere with the interaction between ACE receptor and the viral RBD but not to prevent cell entry of the virus; this may be related to the affinity/avidity of antibodies that is reported to be low after primary infection or first vaccine dose ( 11 , 12 ), and is likely to be even more the case for the population included herein who were sampled 6 months after infection. Despite this low specificity, these assays correlated with the live virus neutralization assay as also found in other studies ( 5 , 6 , 13 , 14 , 15 ). The low specificity could also be attributed to a lack of sensitivity of live VNT but it is rather unlikely that decreasing the threshold below 20 would be clinically relevant, such low titer having little chance to be protective in vivo ( 16 ).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It can be postulated that part of the antibodies detected by these ELISA are able to interfere with the interaction between ACE receptor and the viral RBD but not to prevent cell entry of the virus; this may be related to the affinity/avidity of antibodies that is reported to be low after primary infection or first vaccine dose ( 11 , 12 ), and is likely to be even more the case for the population included herein who were sampled 6 months after infection. Despite this low specificity, these assays correlated with the live virus neutralization assay as also found in other studies ( 5 , 6 , 13 , 14 , 15 ). The low specificity could also be attributed to a lack of sensitivity of live VNT but it is rather unlikely that decreasing the threshold below 20 would be clinically relevant, such low titer having little chance to be protective in vivo ( 16 ).…”
Section: Discussionsupporting
confidence: 83%
“…The study of Von Rein et al ( 22 ) suggested that the correlation between sVNT and VNT was greater at higher level of neutralization titer and they concluded that sVNT are only useful when inhibition was above 50%, which is more consistent with our data. Most of the previous studies used the cPASS assay from GeneSript,showing the correlation of competitive immunoassay to live VNT, with good sensitivity and specificity compared to VNT ( 5 , 6 , 9 , 14 , 15 , 19 , 20 , 22 , 23 ). Only a few studies reported results with the TECO ( 15 , 20 ) or YHLO assays ( 7 , 8 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be postulated that part of the antibodies detected by these ELISA are able to interfere with the interaction between ACE receptor and the viral RBD but not to prevent cell entry of the virus; this may be related to the affinity/avidity of antibodies that is reported to be low after primary infection or first vaccine dose (11,12), and is likely to be even more the case for the population included herein who were sampled 6 months after infection. Despite this low specificity, these assays correlated with the live virus neutralization assay as also found in other studies (5,6,1315). The low specificity could also be attributed to a lack of sensitivity of live VNT but it is rather unlikely that decreasing the threshold below 20 would be clinically relevant, such low titer having little chance to be protective in vivo (16).…”
Section: Discussionsupporting
confidence: 83%